Experimental Investigation for Some Properties of PMMA Denture Base Strengthened by Different Nanoadditives - Alraziqi, Zaynab N. Rasheed; Mansoor, Hadeel Salah (Iraqi Journal of Science, 2020)
In dental and medical applications, poly-methyl methacrylate (PMMA) has been widely accepted due to the excellent biocompatibility and easy fabrication. Yet, some of the physical and mechanical characteristics of this compound are considered inferior. Seven groups of PMMA nano-composite samples were reported to be fabricated at laboratory temperature . These samples could be used in manufacturing the complete or partial maxillary denture base. The aim of this research is to prepare nano-composite materials which consist of PMMA as a matrix material and two different types of powder (prepared nanoparticles of SnO2 and natural egg shell powder (ESP)) as strengthening materials. The selected additives were used in many cases as pure or hybrid composites, specifically with weight percentage ratios of 1 and 2 wt%. Several analytical tests, namely AFM, FTIR, XRD and SEM, were used on the prepared nanoparticles. In addition, several tests were applied to assess the mechanical behavior before and after the reinforcement, including thermal conductivity, Vickers micro-Hardness, and water absorption. The results showed that the maximum amount of energy absorption in the composites was 1% at different types of additives, while a significant increase in thermal conductivity was recorded as the SnO2NPs percentage was increased. For surface micro-hardness, an obvious trend of increase was observed with the increase in additive percentage. The highest measured values of micro-hardness (19.59VHS and 13.30VHS) were recorded for the pure composites of 2% ESP and 2% SnO2, respectively. The results of water absorption test showed that higher percentages of ESP and SnO2, separately, within the pure composite resulted in higher water absorption capacity and an increased value of diffusion coefficient (D).